Efektivitas Intervensi Berbasis Sekolah dalam Meningkatkan Atensi Belajar Siswa - Muhammad Rasyid Ridho; Farah Aulia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This literature review aims to analyze and compare the effectiveness of various school-based intervention programs designed to improve students’ academic attention. Attention is a limited cognitive resource that is vital for Executive Function (EF), which encompasses skills that regulate working memory and inhibitory control. An analysis of 16 research articles classified interventions into three main categories: Mindfulness-Based Interventions (MBIs), Structured Cognitive Training, and Physical Activity Breaks. The review’s findings indicate that MBIs have the highest-quality evidence (Grade A) for improving attention and EF through Internal Attention training, which has been shown to produce Far Transfer improvements in untrained skills, such as social-emotional skills. In contrast, Structured Cognitive Training, which focuses on External Attention, often yields only Near Transfer (improvements on the trained task). Meanwhile, Physical Activity Breaks have proven effective as an attention restoration strategy, particularly when involving cognitive engagement, as supported by Attention Restoration Theory (ART). These findings emphasize that the success of interventions lies in the ability to restore fatigued attention capacity and achieve transfer effects to broader academic domains.